Assessment of Antithrombotic Therapy in Patients with Atrial Fibrillation for 2015-2017 According to the Registry of the Clinic of the Scientific Research Institute of Medical Problems of the North of Krasnoyarsk City - A. A. Tuchkov; N. G. Gogolashvili; R. A. Yaskevich (Рациональная фармакотерапия в кардиологии)
Aim. To evaluate the volume of antithrombotic therapy (ATT) at the prehospital stage in connection with the risk of thromboembolic complications, and also to study the dynamics of the frequency of administration of oral anticoagulants (ОAC) in patients with atrial fibrillation (AF) in 2015-2017.Material and methods. The registry included 562 patients with AF at the age of 18 years and older, hospitalized in the cardiology department during 2015-2017. The registry did not include patients with AF and mechanical heart valves, mitral stenosis. The diagnosis of AF was established in accordance with the current recommendations. All patients had an assessment of the risk of thromboembolic complications on the CHA2DS2-VASc scale, the risk of bleeding on the HAS-BLED scale. The incidence of ATT at the prehospital stage was assessed depending on the risk of thromboembolic complications based on patient questioning and analysis of medical records. In addition, an assessment of the dynamics of the frequency of the OAC prescription during 2015-2017 was conducted.Results. The overwhelming majority of patients with AF (96.1%) belonged to the group of high-risk of cardioembolic strokes according to the CHA2DS2-VASc scale and had indications for OAC therapy. The frequency of OAC prescription in patients with AF who were admitted to the cardiology department was 32% at the prehospital stage, of which 19.8% of patients took warfarin and 12.2% – direct OAC. The target level of the international normalized ratio (from 2.0 to 3.0) at the time of hospitalization was observed only in 33.6% of patients taking warfarin. Over the observation period, there was a tendency to increase the frequency of OAC prescription from 30% in 2015 to 38.4% in 2017.Conclusion. Only 32% of patients with AF and high risk of thromboembolic complications received adequate antithrombotic therapy at the prehospital stage. According to the registry the frequency of OAC prescription in patients with AF during 2015-2017 increased by 8.4%. At the same time, there was a significant increase in the frequency of direct OAC prescription.